Inverse scattering problems and their application to nonlinear integrable equations - Vu, Pham Loi (Vietnam Journal of Mechanics, 2020)
The monograph entitled “Inverse Scattering Problems and Their Application to Nonlinear Integrable Equations” has been published by CRC–Press Taylor Francis Group in November 2019 at the website: https://www.taylorfrancis.com/books/9780429328459. This monograph is devoted to inverse scattering problems for differential equations and their application to nonlinear evolution equations. It contains most of published papers of Prof. Pham Loi Vu, which are mentioned in the Introduction and at the beginning of every chapter of the book. Prof. Dr. Sci. Pham Loi Vu, born in 1934, is a professor of Institute of Mechanics, Vietnam Academy of Science and Technology.